ChemInform Abstract: Revision of the Li—Si Phase Diagram: Discovery and Single‐Crystal X‐Ray Structure Determination of the High‐Temperature Phase Li4.11Si. Issue 7 (18th February 2014) - Zeilinger, Michael; Kurylyshyn, Iryna M.; Haeussermann, Ulrich; Faessler, Thomas F.
Abstract The detailed reinvestigation of the Li‐rich part of the binary Li—Si phase diagram reveals the existence of Li4.106Si (Li16.42Si4) which forms through peritectic decomposition of the Li‐richest phase Li17Si4 at 481—486 °C.